2016
DOI: 10.1038/srep20395
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix stiffness dictates Wnt expression through integrin pathway

Abstract: It is well established that extracellular matrix (ECM) stiffness plays a significant role in regulating the phenotypes and behaviors of many cell types. However, the mechanism underlying the sensing of mechanical cues and subsequent elasticity-triggered pathways remains largely unknown. We observed that stiff ECM significantly enhanced the expression level of several members of the Wnt/β-catenin pathway in both bone marrow mesenchymal stem cells and primary chondrocytes. The activation of β-catenin by stiff EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 40 publications
3
141
0
Order By: Relevance
“…The physiological relevance of culturing SFUs versus salispheres can be extrapolated from these following studies: Srinivasan and colleagues used 3D hyaluronate hydrogel and reported that parotid cells retained their progenitor cell markers (KRT5, KRT14, ETV5, and MYC) and expressed low levels of cell differentiation markers (Srinivasan et al, ). ECM stiffness was reported to activate the integrin/focal adhesion kinase pathway, which in turn activated β‐catenin to increase Wnt1 expression in mesenchymal stem cells and chondrocytes (Du et al, ). The Wnt/β‐catenin pathway was implicated in the maintenance of cell polarization in Mist + pancreatic acinar cells (Pin, Rukstalis, Johnson, & Konieczny, ).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological relevance of culturing SFUs versus salispheres can be extrapolated from these following studies: Srinivasan and colleagues used 3D hyaluronate hydrogel and reported that parotid cells retained their progenitor cell markers (KRT5, KRT14, ETV5, and MYC) and expressed low levels of cell differentiation markers (Srinivasan et al, ). ECM stiffness was reported to activate the integrin/focal adhesion kinase pathway, which in turn activated β‐catenin to increase Wnt1 expression in mesenchymal stem cells and chondrocytes (Du et al, ). The Wnt/β‐catenin pathway was implicated in the maintenance of cell polarization in Mist + pancreatic acinar cells (Pin, Rukstalis, Johnson, & Konieczny, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that stress stimulates the combined expression of vinculin and paxillin, thereby activating FAK[18, 19, 44] to eventually promote the expression of tumor malignancy markers, such as MMP2, MMP9 and VEGF[45]. During mechanotransduction, the Wnt-independent activation of β-catenin is also initiated by FAK upregulation[46] to increase MMP2 and MMP9 activity, thereby contributing to tumorigenesis[47]. FAK signaling pathway also regulates cancer malignancy by modulating ALDH[48] and CD133[49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Wnt signaling and integrin β3 act in a coordinated manner to increase tumorigenesis [46]. Specifically, it has been shown in a mouse model of mammary tumorigenesis that integrin β3 is expressed prominently in transgenic mice with wnt-1 signaling pathway overexpression [30].…”
Section: Discussionmentioning
confidence: 99%